PENGARUH JUMLAH SUDU PADA PROTOTYPE PLTMH DENGAN MENGGUNAKAN TURBIN PELTON TERHADAP EFISIENSI YANG DIHASILKAN - I Gusti Ngurah Saputra; Lie Jasa; I Wayan Arta Wijaya (Program Studi Teknik Elektro UNUD, 2020)
Turbine is a component that plays an important role as an energy converter to be ableto generate electricity in the Micro Hydro Power Plant (MHP). The turbine used in this prototypeis a Pelton tubine. The Pelton turbine is a type of impulse turbine consisting of two blades as aprelude receiver for water jets from the nozzles by utilizing high water heads even though thewater discharge is small. This research will discuss the effect of the number of blades on therotation produced by the Pelton turbine and generator so that it can be seen the voltage,current, power produced that affects the torque value and efficiency obtained on the prototypeMHP. This study aims to obtain a turbine runner with the number of blades that can produce thehighest efficiency, then a variation of the pelton turbine runner is made with different number ofblade parameters from the runner with the number of blades according to the calculationobtained from the reference. Variations in the number of blades used are 14 blades, 16 blades,18 blades, 20 blades, and 22 blades. The results showed that the addition of the number ofblades starting from the smallest caused the performance of MHP to increase, the highestoutput obtained was using a turbine runner with a number of 22 blades which resulted in aturbine rotation of 852.2 rpm before the generator coupled and 497.2 rpm after coupling thegenerator. Generator rotation is 2133.8 rpm, Generator Voltage is 15.72 volts, Generator poweris 33.7 Watts and Torque is 0.6 Nm. The efficiency value using a runner with a number ofblades 22 is 4.54%. The resulting efficiency value is very low because the MHP prototype in generation is less effective and uses a small generation capacity DC generator, so it cannotgenerate power as much as hydraulic power.